Association between Fok1 and TaqI polymorphisms of vitamin D receptor gene with the severity of stenosis and calcification in carotid bulb in patients with ischemic stroke. (March 2022) - Foroughinia, Farzaneh; Morovati, Najmeh; Safari, Anahid; Dianatpour, Mehdi; Jamhiri, Iman; Heydari, Seyed Taghi; Hooshmandi, Sedighe; Borhani-Haghighi, Afshin
Highlights: There was association between carotid calcification with FokI CC polymorphisms of VDR gene. There was no association between severity of carotid stenosis with FokI and TaqI polymorphisms of VDR gene. Targeting vitamin D metabolism at the receptor level for treatment of stroke should be investigated. Abstract: Background and aims: There have been plenty of reports regarding the association between Vitamin D (Vit D) and carotid atherosclerosis and stroke. We aimed to assess the association between FokI and TaqI polymorphisms of vitamin D receptor (VDR) gene and the severity of carotid bulb stenosis and the incidence of carotid bulb calcification in patients with ischemic stroke. Methods: This prospective study conducted at Shiraz University of Medical Sciences between February 2020 and August 2020. All consecutive patients with ischemic stroke with more than 50% carotid bulb stenosis in color doppler sonography underwent cervical CT angiography (CTA). Demographics, risk factors of ischemic stroke, serum calcium, phosphate, creatinine, serum 25-hydroxyvitamin D (Vit D) level were investigated by High-Performance Liquid Chromatography (HPLC) method. The severity of stenosis and presence of calcification in carotid bulb ipsilateral was studied in CTA to ischemic stroke. VDR genotypes of FokI and TaqI polymorphisms were determined by the Restriction Fragment Length Polymorphism (RFLP) method. Results: A total of 122 patients were recruited in this study (mean age: 59.1, 66.4% males, 17.2% with carotid artery stenosis of 70–99%. 57% with carotid bulb calcification). There was a significant association between calcification of carotid bulb with FokI CC polymorphisms of VDR gene (P value = 0.037). There was no significant relationship between the severity of carotid bulb stenosis and Fok1 and TaqI polymorphisms of vitamin D receptor gene and their alleles. Conclusions: There may be a biological association between the FokI VDR gene and carotid bulb calcification.